Endotypes of pollen‐food syndrome in children with seasonal allergic rhinoconjunctivitis: a molecular classification. Issue 8 (6th May 2016) - Mastrorilli, C.; Tripodi, S.; Caffarelli, C.; Perna, S.; Di Rienzo‐Businco, A.; Sfika, I.; Asero, R.; Dondi, A.; Bianchi, A.; Povesi Dascola, C.; Ricci, G.; Cipriani, F.; et al.
Abstract: Background: Pollen‐food syndrome (PFS) is heterogeneous with regard to triggers, severity, natural history, comorbidities, and response to treatment. Our study aimed to classify different endotypes of PFS based on IgE sensitization to panallergens. Methods: We examined 1271 Italian children (age 4–18 years) with seasonal allergic rhinoconjunctivitis (SAR). Foods triggering PFS were acquired by questionnaire. Skin prick tests were performed with commercial pollen extracts. IgE to panallergens Phl p 12 (profilin), Bet v 1 (PR‐10), and Pru p 3 (nsLTP) were tested by ImmunoCAP FEIA. An unsupervised hierarchical agglomerative clustering method was applied within PFS population. Results: PFS was observed in 300/1271 children (24%). Cluster analysis identified five PFS endotypes linked to panallergen IgE sensitization: (i) cosensitization to ≥2 panallergens ('multi‐panallergen PFS'); (ii–iv) sensitization to either profilin, or nsLTP, or PR‐10 ('mono‐panallergen PFS'); (v) no sensitization to panallergens ('no‐panallergen PFS'). These endotypes showed peculiar characteristics: (i) 'multi‐panallergen PFS': severe disease with frequent allergic comorbidities and multiple offending foods; (ii) ' profilin PFS': oral allergy syndrome (OAS) triggered by Cucurbitaceae ; (iii) 'LTP PFS': living in Southern Italy, OAS triggered by hazelnut and peanut; (iv) 'PR‐10 PFS': OAS triggered by Rosaceae ; and (v) 'no‐panallergen PFS': mild disease and OAS triggered by kiwifruit. Conclusions: In a Mediterranean country characterized by multiple pollen exposures, PFS is a complex and frequent complication of childhood SAR, with five distinct endotypes marked by peculiar profiles of IgE sensitization to panallergens. Prospective studies in cohorts of patients with PFS are now required to test whether this novel classification may be useful for diagnostic and therapeutic purposes in the clinical practice.